OPERATIONAL ALTERNATIVES FOR THE INDICES RUFFIER AND RUFFIER - DICKSON - Aurora Cojocaru; Marza Danila Doina (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
The aim of this study was to find another way to calculate the indices Ruffier and Ruffier-Dickson, as part of the evaluation of the organism's adaptive capacity to effort. Discussions After introducing the notion of the image of a pulse ( ), we deduced the formula for calculating the image of the pulse, for each type of pulse, as well the formulas with the images of the pulses, for calculating the indices Ruffier and Ruffier-Dickson. Using the formulas of the images of the pulses, we calculated the values of the images of the pulses and we have included them in a table, to be used in calculating the indices Ruffier and Ruffier-Dickson, through the new formulas. Also for reading the images of the pulses, we made two devices: DI for and DII for , where P1, P2, P3 are respectively the pulse at rest, the pulse immediately after effort, the pulse at 1 minute after cessation of effort. Through numerical examples was found that the results obtained by the classical formulas (with pulses) and by the new formulas (with images of pulses) were the same for each of the two indices (the Ruffier index and the Ruffier-Dickson index). Conclusions Through this study we wanted to offer an alternative to calculating the indices Ruffier and Ruffier-Dickson, with simpler formulas than the classical formulas, using the images of the pulses.